Development policy and economic theory - Basu, Kaushik; Nayak, Pulin (Delhi ; New York : Oxford University Press, 1992)
Seminar papers; in the Indian context.
Includes bibliographical references and index.
Keywords: India -- Economic policy; India -- Economic conditions